2015
DOI: 10.7150/jca.10631
|View full text |Cite
|
Sign up to set email alerts
|

Pathway and Network Approaches for Identification of Cancer Signature Markers from Omics Data

Abstract: The advancement of high throughput omic technologies during the past few years has made it possible to perform many complex assays in a much shorter time than the traditional approaches. The rapid accumulation and wide availability of omic data generated by these technologies offer great opportunities to unravel disease mechanisms, but also presents significant challenges to extract knowledge from such massive data and to evaluate the findings. To address these challenges, a number of pathway and network based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 144 publications
(160 reference statements)
0
33
0
1
Order By: Relevance
“…Higher levels of lipid metabolites, including fatty acids and carnitine metabolites, have been found in breast cancer patients compared to normal controls (35,38,42). Wang et al (9) reported that several lipids including phosphatidylglycerol (PG) were upregulated in highly invasive breast cancer cells. Breast tumors are described as developing a ‘lipogenic phenotype’, and while cell growth is dependent on lipogenesis, lipolysis is upregulated, and is associated with tumor aggressiveness (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of lipid metabolites, including fatty acids and carnitine metabolites, have been found in breast cancer patients compared to normal controls (35,38,42). Wang et al (9) reported that several lipids including phosphatidylglycerol (PG) were upregulated in highly invasive breast cancer cells. Breast tumors are described as developing a ‘lipogenic phenotype’, and while cell growth is dependent on lipogenesis, lipolysis is upregulated, and is associated with tumor aggressiveness (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…This latter growing technology permits simultaneous monitoring of thousands of macro and micro metabolites that serve as substrates and products of metabolic pathways (8). Integration of these pathways and their interactions provides insight into the development of malignant processes and could lead to the discovery of cancer biomarkers (9). …”
Section: Introductionmentioning
confidence: 99%
“…[31] More recent efforts at integrating -omics data for identification of targetable signaling modules have taken divergent approaches, including by multiple hypothesis testing as described here. [32] To our knowledge, a cross-platform and genome-wide search for unexpected alterations that may correlate with increased pSTAT3(Y705) expression in HNSCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology focuses in understanding large-scale data derived from highthroughput techniques into comprehensive predictive models, quantifying all molecular entities (proteins or genes) of a biological system to evaluate their interactions into networks [18,19]. The behavior of these networks may be considered as a biomarker, as showed by models for cancer [20] and other diseases, such as respiratory illness [21][22][23][24]. Thus, the aim of this study is to identify a major network as a biomarker for CR in asthma, which may help to early distinguish patients with severe ashtma and to define new therapeutic targets to be explored.…”
Section: Introductionmentioning
confidence: 99%